Self-Crosslinking Lipopeptide/DNA/PEGylated Particles: A New Platform for DNA Vaccination Designed for Assembly in Aqueous Solution - Joan K. Ho; Paul J. White; Colin W. Pouton (Elsevier, 2018)
Delivery of plasmids for gene expression in vivo is an inefficient process that requires improvement and optimization to unlock the clinical potential of DNA vaccines. With ease of manufacture and biocompatibility in mind, we explored condensation of DNA in aqueous solution with a self-crosslinking, endosome-escaping lipopeptide (LP), stearoyl-Cys-His-His-Lys-Lys-Lys-amide (stearoyl-CH2K3), to produce cationic LP/DNA complexes. To test whether poly(ethylene glycol) (PEG)-ylation of these cationic complexes to neutralize the surface charge would improve the distribution, gene expression, and immune responses poly(ethylene glycol), these LP/DNA complexes were combined with 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG2000). Fluorescence imaging illustrated that the cationic complexes exhibited the highest degree of localization and lowest degree of dispersion throughout the injected muscle, suggesting impaired mobility of cationic particles upon administration. Nanoluciferase reporter assays over a 90-day period demonstrated that gene expression levels in muscle were highest for PEGylated particles, with over a 200-fold higher level of expression than the cationic particles observed at 30 days. Humoral and cell-mediated immune responses were evaluated in vivo after injection of an ovalbumin expression plasmid. PEGylation improved both immune responses to the DNA complexes in mice. Overall, this suggests that PEGylation of cationic lipopeptide complexes can significantly improve both the transgene expression and immunogenicity of intramuscular DNA vaccines. Keywords: DNA vaccine, PEGylation, lipopeptide, intramuscular, non-viral gene delivery, gene expression, humoral and cell-mediated immunity